A HARZARD ANALYSIS ON FACTORS ASSOCIATED WITH THE CHOLERA OUTBREAK OF JANUARY TO MARCH 2000 IN BUHERA DISTRICT: MANICALAND PROVINCE, ZIMBABWE - Miriam Chitura (European Scientific Journal, ESJ, 2014)
Cholera is an acute diarrhoeal disease caused by bacteria called vibrio cholerae. It has a high case fatality rate. Cholera is endemic in Zimbabwe and the country experiences cholera epidemics during the rainy season. A case control study was conducted following an outbreak of cholera in Buhera District of Manicaland Province in Zimbabwe. Interview schedules, observation methods and laboratory analysis of stool specimens were used to collect data. A 100% response rate was achieved from 40 cases and 80 controls. Significant risk factors, among others, included lower level education, odds ratio (OR) =4.6, Confidence Interval (CI) =1.83 -12.8 P-value =<0.001; attending gatherings, OR= 2.25,CI=0.97 -5.26,P=0.038; communal hand washing OR=3.86,C I=1.14- 14.37, P=0.015 The epidemic curve indicated a point source infection. The findings indicated a strong association between poor hygiene and sanitation with the spread of cholera. Cholera was first shown to be water-borne by a proper epidemiological study by John Snow in East London. Traditionally, water was recognised as the primary vehicle for transmission of cholera, but in the past 30 years, outbreaks of cholera associated with eating contaminated food have demonstrated that food also plays an important role. However, vehicles for transmission vary from place to place and this is affected by local customs and practices, and hence, selection of control and preventive measures that are most suitable locally must be implemented.